The Attitude Of Agricultural Extension Workers Toward The Use of Digital Population Identity In The Distribution of Subsidized Fertilizer In Maros Regency - Halim, Abdul; Faisal, Muhamad; Halim, Khairunna Istiqamah (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2025)
This study aims to analyze the attitude of agricultural extension workers toward the use of Digital Population Identity (Indonesian: Identitas Kependudukan Digital [IKD]) in the distribution of subsidized fertilizer in Maros Regency. This research employed a quantitative approach, using a questionnaire as the primary instrument. The samples consisted of 66 agricultural extension workers residing in Maros Regency, selected through purposive sampling. Data analysis was conducted using SPSS for Windows 23, incorporating Spearman’s rank correlation analysis and the Mann-Whitney U test. The results indicate as follows: (1) Factors influencing the attitude of agricultural extension workers include personal experience, the influence of significant people, and exposure to mass media, which fall into the low to moderate category; formal education falls into the high category, while non-formal education is in the low category. (2) Agricultural extension workers generally agree with the use of IKD in the distribution of subsidized fertilizer, both during the registration of farmers eligible for subsidies and during the verification and validation of farmer data when redeeming subsidized fertilizer. (3) Personal experience, the influence of significant people, and exposure to mass media do not have a significant relationship with agricultural extension workers’ attitudes toward the use of IKD. However, formal and non-formal education significantly correlate with their attitudes toward IKD implementation. (4) There is no significant difference in attitudes toward IKD use between agricultural extension workers who are digitally adaptive and those who are not. However, there is a significant difference in attitude toward IKD use between agricultural extension workers with an S2 (master’s) degree and those with an S1 (bachelor’s) degree. Additionally, a significant difference exists between agricultural extension workers who have attended a high level of non-formal education and those with a low level of non-formal education.